The Influence of Political Awareness, Political Socialization, and Mass Media on Political Participation in Jambi Province - Irzal Anderson; Kuswanto Kuswanto (FISIP Universitas Islam Negeri Raden Fatah Palembang, 2021)
The purpose of this study was to determine the effect of political awareness, political socialization and mass media on the political participation of the people of Jambi Province in the regional head election. Political participation is a form of community involvement in exercising their political rights in general elections both at the national and regional levels. The embodiment of political rights will affect every decision-making related to the interests of the community. This study uses a quantitative approach that uses statistical techniques with PLS model analysis techniques. The study was conducted on the people of Jambi City as many as 100 people were selected based on area sampling techniques. The research findings explain that the mass media has no direct effect on political participation. Political participation is directly influenced by the variables of Political Awareness and Political Socialization. Therefore, it is suggested that the use of mass media in the post-conflict local election in Jambi Province needs to be improved, especially information related to the political rights of the community. The tendency that occurs in the community is more interested in obtaining information related to entertainment because people are still accustomed to listening culture rather than reading culture.